Niveles de palmiste y maracuya en el engorde de dos razas de pollos broilers - Carranza Olmedo, Julio Arturo (2015)
This research, entitled "Levels Palmiste And Passion In The Fattening Broiler Chickens Two Races" was held on the farm "La Juliana" urban parish Quevedo Canton Venus, on the farm owned by Mr. Julio Carranza. Geographic coordinates: Latitude South 1st 1 '36 "west longitude and 79 ° 27' For this research set basic parameters for raising broilers are taken as Weight gain and feed conversion and also the respective economic analysis. The research was evaluated using descriptive statistics, within the parameters of normal Gaussian curve, in order to determine the behavior of both Hubbard and Arbor Acres study lines, similarly verify the benefits of two cakes of agricultural products are: passion fruit and palm kernel. A level cakes are best results for passion fruit replacing balanced reached 15% to 3488.33 grams of an increase in average chicken compared to palm kernel level of 15% replacement reached to 3038.33 grams balanced weight increase with Hubbard chickens line, while the line of Arbor acres chickens, passion fruit cake obtained the best weight increases with levels reached 15 and 20% increases in 3542.667 grams and 3546 grams respectively. At the level of the Arbor Acres feed conversion line on average within 8 weeks of research I had an average of 2.24 while the line of chickens Hubbard reached on average 2.33 units of consumption per unit of weight increase. In the economic evaluation: The T12 and T11 treatments Arbor Acres line scored the best returns that reached 37.97 and 37.84%, respetivamente. Key words: I increase of weight, nutritious conversion and profitability.